Building bridges: how hospitality can foster positive peace - Latifa Benhadda; Rainer Prasetya (Research in Hospitality Management)
This opinion piece explores the relationship between hospitality and positive peace from a social and ethical perspective, focusing on human dignity, justice and care. It argues that hospitality, beyond its commercial lens, should be viewed through the interaction between host and guest. Despite global unrest, human connection through travel persists, refugees and migrants numbers increase, revealing hospitality as a powerful but often overlooked tool for peacebuilding in different types of host and guest interactions. We examine how emotional interaction in commercial hospitality can be a trigger for positive peace. We shed light on Kant’s and Derrida’s concepts of conditional and unconditional hospitality and their impact on positive peace, and elaborate on how calibrated reciprocity can lead to positive peace, despite the challenges. We also discuss dialogical hospitality as a means of fostering understanding and resolving misconceptions. Additionally, we explore the risks that weaken hospitality’s ability to resolve conflicts, ultimately proposing that hospitality is not only a human phenomenon, but also a critical path to achieving sustainable positive peace. In the context of migration, refugee crises and wars, hospitality is seen as a moral duty, essential for building long-term peace. In conclusion, we suggest that positive peace requires going beyond tolerance to create a culture where every individual, regardless of origin, is treated with dignity. Hospitality is framed as a responsibility in a world in need of positive peace.